The Mother-Child Relationship in Efforts to Form Spiritual Intelligence in Divorce Families - Azzahro, Mar'i Sophia; Rahmatullah, Azam Syukur (FKIP Universitas Lampung, 2025)
The Mother-Child Relationship in Efforts to Form Spiritual Intelligence in Divorce Families. This study aims to determine and analyze the relationship between mothers and children to build spiritual intelligence in divorced families at SMK Muhammadiyah Prambanan in Sleman, Yogyakarta. In addition, this study seeks to understand the dynamics of mother-child relationships that arise from divorced families and to identify the supporting and inhibiting factors affecting these relationships in efforts to enhance spiritual intelligence. The research approach employed is a phenomenological study. The research subjects were determined by the researcher and a teacher at the school, along with recommendations from other teachers and staff at SMK Muhammadiyah Prambanan in Sleman, Yogyakarta. Data was collected using techniques such as observation, interviews, and documentation. The collected data will then be analyzed using phenomenological data analysis techniques. The results indicated that a strong relationship between mothers and children, despite coming from a divorced family, can foster positive spiritual intelligence in children, as evidenced by the positive behaviors of the three mother-child pairs recognized by the school environment and community, despite their circumstances. Various efforts must be made to cultivate a positive relationship between mothers and children, particularly in establishing healthy communication. The supporting factors for the mother-child relationship in developing children's spiritual intelligence in divorced families include the mother's role, the child's condition, and the school environment. Meanwhile, the inhibiting factors consist of the relationship between parents after divorce and public perceptions of divorced families. Keywords: mother-child relationship, spiritual intelligence, divorced family.